2017
DOI: 10.1158/0008-5472.can-16-3310
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear NMR and MRI Reveal an Early Metabolic Response to mTOR Inhibition in Sarcoma

Abstract: Biomarkers predicting rapalog responses in sarcomas where PI3K and mTOR are often hyperactivated could improve the suitable recruitment of responsive patients to clinical trials. PI3K/mTOR pathway activation drives energy production by regulating anaerobic glycolysis in cancer cells, suggesting a route toward a monitoring strategy. In this study, we took a multi-modality approach to evaluate the phenotypic effects and metabolic changes which occur with inhibition of the PI3K/mTOR pathway. Its central role in r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…7,26 Moreover, mTOR pathway activation has been reported to promote tumour cell capacitation through anaerobic glycolysis, and mTOR pathway inhibitors have been demonstrated to inhibit tumour cell growth when combined with existing chemotherapeutic agents. 27 LKB1 forms a heterotrimeric complex with ste20-related adaptor and CAB39. 10 LKB1 tumour-suppressor activity is caused partly by AMPK-mediated inhibition of inappropriate mTOR activation.…”
Section: Discussionmentioning
confidence: 99%
“…7,26 Moreover, mTOR pathway activation has been reported to promote tumour cell capacitation through anaerobic glycolysis, and mTOR pathway inhibitors have been demonstrated to inhibit tumour cell growth when combined with existing chemotherapeutic agents. 27 LKB1 forms a heterotrimeric complex with ste20-related adaptor and CAB39. 10 LKB1 tumour-suppressor activity is caused partly by AMPK-mediated inhibition of inappropriate mTOR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased flow through the glycolytic pathway due to treatment with TMZ in a preclinical GB model had also been detected, but in this instance the reduced Lac/Pyr ratio after injection of hyperpolarized Pyr was caused not by LDHA expression changes but by downregulation of the M2 isoform of the pyruvate kinase enzyme (PKM2). Furthermore, mTOR inhibition alone in a preclinical xenograft model of sarcoma also resulted in a reduced Lac/Pyr ratio after injection of hyperpolarized Pyr, 24 h after the mTOR inhibitor administration (rapamycin) and prior to any anatomic detectable changes …”
Section: Mrs(i)‐detectable Metabolic Hallmarks Of Cancer: Applicationmentioning
confidence: 98%
“…Sensitivity enhancement achieved by hyperpolarization of nuclei of a metabolic tracer offers the possibility of using noninvasive magnetic resonance spectroscopy (MRS) and MRI to measure fluxes through individual enzyme-catalyzed reactions. In sarcoma animal models it was observed that quantitative reduction in lactate production after administration of hyperpolarized pyruvate as monitored by hyperpolarized MRI followed the tumor size changes and was useful for monitoring of therapy in this setting [168]. Another study showed the usefulness of this approach in canine patients with sarcomas [169].…”
Section: Molecular Imaging and Theranostic Strategies For Diagnosis Amentioning
confidence: 99%